Mapping arsenopyrite alteration in a quartz vein-hosted gold deposit using microbeam analytical techniques. (2nd January 2018) - Gilligan, M.; Costanzo, A.; Feely, M.; Rollinson, G. K.; Timmins, E.; Henry, T.; Morrison, L.
Abstract: An unworked quartz vein-hosted gold deposit occurs in the Clew bay area of County Mayo, western Ireland. The veins are late-Caledonian in age and transect greenschist-facies poly-deformed Silurian quartzites. The veins contain disseminated arsenopyrite that may be a primary mineral source for elevated levels of arsenic (As) found in groundwater samples recovered from wells related spatially to the gold deposit. Levels from 5 to 188 μg/L (significantly above the 7.5 μg/L threshold for safe drinking water) have been detected. A series of element distribution maps using a scanning electron microscope (Hitachi model S-4700) linked to an energy-dispersive spectrometer (INCA ® Oxford Instruments) and mineral distribution maps generated by QEMSCAN ® (Quantitative Evaluation of Minerals by Scanning electron microscopy) were used to map the distribution of the primary arsenopyrite and related secondary As-bearing phases. Laser Raman microspectroscopy was used to identify the secondary As-bearing phases. 'Island weathering' of primary arsenopyrite together with hydrated pseudomorphs of arseniosiderite, pharmacosiderite and scorodite after arsenopyrite are recorded. Circulating groundwater hydrates the primary arsenopyrite, providing the release mechanism that forms the secondary As-bearing phases that occur as microfracture infills together with muscovite and biotite. The textural relationships between the primary and secondary As minerals indicate their potential as mineral sources of As that could enter transport pathways leading to its release into groundwater.